Analisis Kesulitan Mahasiswa tentang Pembelajaran Pecahan pada Kitab Faroid - Netriwati, Netriwati (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
The phenomenon that occurs in students is the difficulty of them in detailing and sorting out the division of inheritance. In Islam everything is set up but its application in daily life has not been done with that should be. After the authors delve deeper into this material is indeed difficult to understand, especially in the details of each received by the heirs very closely related to the learning of mathematics in sub-material fractions. Lack of time allocation used in this material, resulting in them not getting examples of varied questions. The method used is qualitative descriptive method. This method tries to describe and interpret what is in accordance with the growing conditions in the ongoing process. Based on the phenomenon that occurred in the field can be concluded that the difficulties experienced by students is to determine the parts that must be accepted by the heirs that have been set in the Qur'an difficult to apply in everyday life, Islam has set clearly in the Qur'an But this has not been done properly. Another difficulty is also experienced in the learning of mathematics is on the equalization pemyebut of fractions obtained by heirs who are too many are entitled to receive inheritance.Keywords: